Families Living with Blood-Borne Viruses: The Case for Extending the Concept of “Serodiscordance” - Persson, Asha; Newman, Christy E.; Hamilton, Myra; Bryant, Joanne; Wallace, Jack; valentine, kylie (Interdisciplinary Perspectives on Infectious Diseases, 2017)
The concept of “serodiscordance” (mixed infection status) is primarily associated with epidemiological concerns about HIV transmission risk in couples. We make the case for extending this concept to include families with mixed HIV and viral hepatitis status. Social research on couples with mixed HIV and hepatitis C status has laid an important foundation for illuminating how experiences of serodiscordance within intimate partnerships are much broader than concerns about risk. This body of work attests to serodiscordance holding promise as a valuable concept for understanding viral infections as socially situated and intensely relational phenomena. However, serodiscordance is still limited as a concept because of its near universal focus on couples. It is rarely applied to wider relationships, including family networks beyond the couple. Despite evidence in the literature that families are affected by blood-borne viruses in multiple social, emotional, financial, and generational ways, the concept of serodiscordance does not capture these broader dynamics. Making serodiscordance more inclusive is an important step in recognising the diverse ways families’ everyday lives, relationships, and futures can be entangled with HIV, hepatitis C, and hepatitis B, and for understanding how today’s era of effective treatment options might shape the “family life” of viral infections.